2021
DOI: 10.1371/journal.pone.0252760
|View full text |Cite
|
Sign up to set email alerts
|

Variation in outcome of invasive mechanical ventilation between different countries for patients with severe COVID-19: A systematic review and meta-analysis

Abstract: Background COVID 19 is the most recent cause of Adult respiratory distress syndrome ARDS. Invasive mechanical ventilation IMV can support gas exchange in patients failing non-invasive ventilation, but its reported outcome is highly variable between countries. We conducted a systematic review and meta-analysis on IMV for COVID-associated ARDS to study its outcome among different countries. Methods CENTRAL, MEDLINE/PubMed, Cochrane Library, and Scopus were systematically searched up to August 8, 2020. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Mortality in our cohort (28%) coincided with the wide range of mortality reported in a systematic review and meta-analysis of 37,359 patients. 22 Although mortality in our cohort was relatively lower than that in other studies, 23 27 this finding cannot be generalized owing to the small number of patients and because of the collapsed state of the health care system when the COVID epidemic was at its peak in Slovakia. As a result, many patients were only stabilized using PMLV until such time as they could be transferred (while still on the ventilator) to other peripheral hospitals where weaning was commenced.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Mortality in our cohort (28%) coincided with the wide range of mortality reported in a systematic review and meta-analysis of 37,359 patients. 22 Although mortality in our cohort was relatively lower than that in other studies, 23 27 this finding cannot be generalized owing to the small number of patients and because of the collapsed state of the health care system when the COVID epidemic was at its peak in Slovakia. As a result, many patients were only stabilized using PMLV until such time as they could be transferred (while still on the ventilator) to other peripheral hospitals where weaning was commenced.…”
Section: Discussioncontrasting
confidence: 74%
“…In comparison, several other studies from the same period or later have reported longer lengths of ICU stay, ranging from 10 to 15 days. [19][20][21][22] Whether these differences arise owing to the PMLV mode used in our study is an important area of further research. Any mode of ventilation that is closer to the physiological needs of the patient has the potential to reduce the length of stay in the ICU and would thus positively affect resource distribution, especially during periods of immense pressure on ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall ICU mortality in the preexisting literature on COVID-19 varies greatly depending on the geographic location, the period of analysis and the clinical characteristics of the analyzed cohort and ranges between 21 and 100% [ 41 43 ]. A German study performed in 2020 in ventilated patients reported a mortality of 38.8% [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients critically ill with coronavirus disease 2019 (COVID-19) often require mechanical ventilation and prolonged hospitalization duration to restore adequate gas exchange and to alleviate acute respiratory distress syndrome (ADRS) [ 1 ]. There is variability between individual studies with respect to frequency of ARDS caused by COVID-19 [ [2] , [3] , [4] ]; individual studies for which data is available indicate that among hospitalized COVID-19 patients, approximately 1/3 (33%) develop ARDS, 1/4 (26%) require transfer to an intensive care unit (ICU), and 1/6 (16%) receive invasive mechanical ventilation [ 5 ]. Injury to the brain - whether secondary to systemic (respiratory system) dysfunction, neuro-vascular damage, or direct neural-invasion (e.g., via the olfactory nerve) [ 6 ] contributes to COVID‐19 pathophysiology, symptoms, and progression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%